3 Dimensional data research for property valuation in the context of the LADM Valuation Information Model. (November 2020) - Kara, Abdullah; van Oosterom, Peter; Çağdaş, Volkan; Işıkdağ, Ümit; Lemmen, Christiaan
Highlights: Three-dimensional (3D) information can be used in order better to estimate and explain values of property units. Recording derived locational and environmental characteristic of property unit into property valuation registries may prevent loss of time and of labor. Property valuation domain are not widely benefiting from the 3D models and 3D datasets to derive external characteristics of property unit except for visibility analysis. Abstract: Property valuation is a process that promotes sustainable development as it supports and forms several land management activities. Access to information on the legal, geometric, physical, locational and environmental characteristics of property units together with the economic indicators are required for an effective property valuation system. Traditional cadastral systems generally provide only two-dimensional (2D) legal and geometric information about property units, however, today's valuation practices would benefit significantly from three-dimensional (3D) information in order better to estimate and explain values of property units. The purpose of this paper is to examine how 3D spatial datasets and spatial analyses have been used in property valuation, and to develop 3D valuation unit profile(s) in line with the examination results for the recently proposed Valuation Information Model that extends the ISO 19152:2012 Land Administration Domain Model (LADM) from the valuation point of view. The study focuses more on 3D locational and environmental characteristics of property units; particularly visibility and especially viewshed analysis in terms of property valuation. By using open topography, building and height datasets of the Netherlands, a number of viewshed analyses are conducted to show how it can be utilized using different 3D data sources. The main contribution of the article is to present how 3D datasets and spatial analyses could be used to support property valuation activities and to investigate to what extent it is possible and meaningful to include derived 3D characteristics of property units in valuation registries.